A Short History of the Roman Mass. By Uwe Michael Lang. San Francisco: Ignatius Press, 2024. 146 pp. ISBN: 978-1-62164-697-6, $ 17.95 paper - Malesevic, Filip (Church history, 2025)
A Short History of the Roman Mass. By Uwe Michael Lang. San Francisco: Ignatius Press, 2024. 146 pp. ISBN: 978-1-62164-697-6, $ 17.95 paper - Volume 94 Issue 2